PCR-based CRISPR/Cas9 system for fluorescent tagging: A tool for studying Candida parapsilosis virulence - Tibor Nemeth; Andrea Zarnocki; Anett Ladanyi; Csaba Papp; Ferhan Ayaydin; Gabor Janos Szebeni; Attila Gacser (PLoS ONE, 2025)
Candida parapsilosis is persistent in a hospital environment hence it is often associated with nosocomial infections especially amongst low-birth weight neonates. Genetic modification is therefore important to characterise the physiological and virulence related properties of this fungus. A PCR-based CRISPR/Cas9 system has been adopted to facilitate the generation of fluorescent tagged prototroph isolates. We examined a total of eight fluorescent protein coding genes, out of which three were found to be applicable for simultaneous utilisation. We investigated three clinical isolates of C. parapsilosis in terms of their adherence to silicone and their uptake by J774.2 murine macrophages in competition assays. Interestingly, we found significant differences between them in both experiments where GA1 isolate was significantly less resistant to macrophage uptake and CDC317 was significantly more adherent to silicone material. In silico analysis of the agglutinin-like sequences (Als) exposed remarkable diversity in this protein family and additionally, the thorough analysis of the ALS genes revealed evidence of formation of a new gene by intrachromosomal recombination in the GA1 isolate. Finally, we provide a step by step protocol for the application of the PCR-based CRISPR/Cas9 system for fluorescently labelling C. parapsilosis isolates.